'I wondered does this make me any less of a teacher …?' Early childhood teachers in Aotearoa New Zealand claimed by and claiming authority within a dominant discourse. (June 2014) - Warren, Alison
Early childhood teachers in Aotearoa New Zealand negotiate their personal professional identities within the context of a nationally organised and regulated education sector. Early childhood teaching has become increasingly professionalised. Emphasis on qualifications and professional standards has constrained possible ways of being early childhood teachers. This article discusses two newly qualified teachers' perceptions of claiming and being claimed by authority as they engaged in facilitated self-study. These teachers were participants in a post-structural qualitative collective case study that was a master's thesis study. They had recently graduated from a field-based initial teacher education course, so they had been practitioners in early childhood settings while student teachers. The dominant authority discourse that emerged from data positioned these teachers as claimed by authority of qualification requirements and hierarchical professional relationships, and as claiming authority as knowledgeable and responsible teachers. I propose that these two participants' ways of being teachers were constrained by disciplinary discursive practices within the authority discourse. They also actively negotiated their personal professional identities within the authority discourse through seeking pleasure, resistance to positioning and through negotiation of their subjectivities. I suggest that early childhood teachers and teacher educators should critically reflect on how the dominant authority discourse limits possible ways of being teachers in Aotearoa New Zealand, and consider whether this discourse unfairly excludes some people from the teaching profession to the detriment of practitioners, parents and families, and children.